2019
DOI: 10.1182/blood.2019000644
|View full text |Cite
|
Sign up to set email alerts
|

CD137 deficiency causes immune dysregulation with predisposition to lymphomagenesis

Abstract: Somekh and colleagues identify CD137, a member of the tumor necrosis factor superfamily, as a novel cause of immunodeficiency associated with a risk of autoimmunity and lymphoid malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 27 publications
(32 reference statements)
2
60
0
Order By: Relevance
“…Accordingly, all 4 patients analyzed by Somekh et al had increased proportions of immature B cells and decreased proportions of memory B cells and plasmablasts and abnormal immunoglobulin levels. 9 This phenotype was also observed in the two patients analyzed by Rodriguez et al, where memory B cell numbers were severely reduced. 10 Although B cell subsets were not analyzed by Alosaimi et al, low IgG and high IgM levels, and a poor antibody response to tetanus toxoid and an absent recall response to pneumococcal polysaccharide vaccine, in one of the two patients indicate a disturbance in B cell maturation.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…Accordingly, all 4 patients analyzed by Somekh et al had increased proportions of immature B cells and decreased proportions of memory B cells and plasmablasts and abnormal immunoglobulin levels. 9 This phenotype was also observed in the two patients analyzed by Rodriguez et al, where memory B cell numbers were severely reduced. 10 Although B cell subsets were not analyzed by Alosaimi et al, low IgG and high IgM levels, and a poor antibody response to tetanus toxoid and an absent recall response to pneumococcal polysaccharide vaccine, in one of the two patients indicate a disturbance in B cell maturation.…”
supporting
confidence: 61%
“…Somekh et al also analyzed Tfh numbers and found reduced counts in 3 of the 4 patients. 9 These findings clearly document the importance of CD137 -CD137L interaction for the humoral immune response.…”
mentioning
confidence: 71%
See 3 more Smart Citations